Instructional Leadership Practices for Effective Formative Assessment at Primary Level (Journal of Asian Development Studies, 2024)
Instructional leadership practices are vital in shaping quality education and improving outcomes of students. It ensures that the vision of the school is focused on academic excellence and holistic development, benefiting the learners, teachers, and the broader educational community. The current study investigates the instructional leadership practices that support effective formative assessment in primary education focusing on principals’ and teachers’ roles in enhancing the learning of students. The objectives are threefold highlighting the principals’ self-reported practices, understanding teachers’ perspectives, and examining discrepancies between the views of head teachers and teachers on formative assessment practices. Adopting a quantitative research approach, data was collected through a structured questionnaire. The tool includes 17 items. Data was collected from a sample comprising 34 principals and 48 teachers across both public and private sector primary schools within the District Lahore. The collected responses were analyzed using SPSS with descriptive statistics highlighting a shared understanding among educational leaders and teachers. Findings suggest that diverse assessment techniques, collaborative discussions, and consistent monitoring of student’s progress are vital to effective formative assessment. The study recommends practices such as peer resource activation, meetings regularly focusing on students’ learning outcomes and active engagement by principals in evaluating the tasks of students. These strategies underscore the instructional leaders’ crucial role in fostering a supportive environment for student assessment and development, with implications for both public and private education settings.